Photoautotrophic production of renewable ethylene by engineered cyanobacteria: Steering the cell metabolism towards biotechnological use - Kallio Pauli; Kugler Amit; Pyytövaara Samuli; Stensjö Karin; Allahverdiyeva Yagut; Gao Xiang; Lindblad Peter; Lindberg Pia (WILEY, 2022)
Ethylene is a volatile hydrocarbon with a massive global market in the plastic industry. The ethylene now used for commercial applications is produced exclusively from nonrenewable petroleum sources, while competitive biotechnological production systems do not yet exist. This review focuses on the currently developed photoautotrophic bioproduction strategies that enable direct solar-driven conversion of CO2 into ethylene, based on the use of genetically engineered photosynthetic cyanobacteria expressing heterologous ethylene forming enzyme (EFE) from Pseudomonas syringae. The emphasis is on the different engineering strategies to express EFE and to direct the cellular carbon flux towards the primary metabolite 2-oxoglutarate, highlighting associated metabolic constraints, and technical considerations on cultivation strategies and conditional parameters. While the research field has progressed towards more robust strains with better production profiles, and deeper understanding of the associated metabolic limitations, it is clear that there is room for significant improvement to reach industrial relevance. At the same time, existing information and the development of synthetic biology tools for engineering cyanobacteria open new possibilities for improving the prospects for the sustainable production of renewable ethylene.